Analysing Differences in Attack Indicators in Men's First Division Volleyball According to the Positional Status of Teams - George Danut Mocanu; Neculai Harabagiu; Carmen Parvu (OVS LLC, 2024)
Background. Attack efficiency in the game of volleyball is of paramount importance in winning competitions. Objectives. The study aimed to analyse the differences in attack efficiency between teams of varying value levels, according to their position in the ranking. Materials and methods. All 12 teams participating in the men's national first league championship were analysed using the Data Volley software. The attack parameters were compared between teams in the first half of the ranking vs teams in the second half. Another comparison was performed for 3 value levels of the top teams (top, middle, and low).   Results. The Mann-Whitney U test (used to assess the differences between teams in the first half vs. teams in the second half of the ranking) indicates Z values associated with statistically significant thresholds (p〈 0.05) for most of the attack indicators, except Blocked but recovered% (p 〉0.05). The situation is similar also for the Kruskal-Wallis test, where χ² values indicate significant differences between the three levels of the teams for most of the parameters, except Blocked but recovered%. Conclusions. The findings reveal the higher values of attack efficiency and its parameters for the teams placed in the top positions of the ranking. The teams in the first half of the ranking have better percentage values on the executions associated with Winning% and Positive%. The attacking players of these teams also demonstrate lower percentage scores on the executions associated with Error%, Blocked attack% and Poor%, thus committing fewer mistakes. The situation is similar when comparing the top vs low and middle vs low pairs, where only for Blocked but recovered% no significant differences have been identified. These results support the need to focus on making the volley attack more efficient as a decisive factor in competitive success.